Tanggung Jawab Pemerintah Terhadap Revitalisasi Trotoar Di Kota Ambon - Irfan Prawira Idris; Merry Tjoanda; Theresia Louize Pesulima (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Sidewalks function as road facilities that can support various community activities as pedestrians walk on the highway. Law Number 22 of 2009 concerning Road Traffic and Transportation has clearly accommodated the provision of protection for the rights of pedestrians in Indonesia in which every Indonesian society as pedestrians has the right to the availability of the sidewalk. Article 3 of the UUPK states that one of the objectives of consumer protection is to create an element of legal protection that contains legal certainty for consumer rights, including the right to use safe and comfortable sidewalk facilities. above, often in several areas in Indonesia many pedestrians complain about sidewalk facilities that are not functioning properly. The sense of security and comfort that pedestrians get, is inversely proportional. One of them is the revitalization of sidewalks in the city of Ambon, which turned out to be slippery and caused losses for road users.Purposes of the Research: The purpose of this study is to identify and explain the government's responsibility for increasing user fees in Ambon City. Methods of the Research: The method used in this research is a normative juridical method with a statutory approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials. The legal materials were analyzed qualitatively in order to answer the problems studied.Results of the Research: Based on the results of the study, it shows that the Government in this case the Department of Public Works and Spatial Planning of the Maluku Province is also responsible for the losses experienced by the community as pedestrians as a result of revitalizing the slippery pavement and does not provide a sense of security, comfort and maintain pedestrian safety. Therefore, pedestrians who suffer losses due to the slippery pavement can take legal action to demand compensation from the government, both litigation and non-litigation.